Heteroepitaxy of Ga2(1‑x)In2xO3 layers by MOVPE with two different oxygen sources. Issue 8 (30th July 2014) - Baldini, M.; Gogova, D.; Irmscher, K.; Schmidbauer, M.; Wagner, G.; Fornari, R.
<x xml:space="preserve">Abstract</x> The subject of this paper is the epitaxial growth of thin films of gallium‐indium oxide (Ga2(1−x)In2xO3), a transparent semiconducting oxide. The effects related to the use of oxygen and water as oxygenation sources were investigated. With oxygen, independently from the amount of In incorporated in the layers, phase separation of the two binary oxides was observed. With water, on the other hand, no In2O3 phase occurred up to x∼0.25, and the layers showed improved surface morphology. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>